READING THE VALUES OF LIBERAL FEMINISM IN HILLARY CLINTON’S SPEECH AT THE DEMOCRATIC NATIONAL CONVENTION 2016 - Andra Fakhrian; Dini Nur Islamiyati (OKARA: Jurnal Bahasa dan Sastra, 2017)
In history, Hillary Clinton is the only female candidate as the president of the United State, and she got the name in politic, and having significant roles as a politician in America. Hillary performs a strong leadership and how the picture of women in the modern era. Thus, this study examines the representative women in the lens of Hillary Clinton. It is also under descriptively qualitative research supported by primary data from the script of Hillary Clinton’s speech at the democratic national convention 2016 along with relevant literature as the secondary data. The theory of liberal feminism is used to get a deep analysis of the women’s roles in modern society. Now Women seize the same chance for involving their roles in modern society. Women are not only in a domestic sense, but also in masculinity areas.